(untitled) (Research, Society and Development, 2025)
The Standard Operating Procedure (SOP) is an official document whose purpose is to reduce the margin of error of public security agents as they handle everyday situations in a detailed manner, providing guidance on the best course of action without restricting the professional’s discretion. In this regard, its implementation enables the achievement of desirable results in terms of professionalism and legal certainty within the operational environment. The general objective of this study was to demonstrate the importance of standardizing SOPs, emphasizing the digitalization and expansion of the access system of the Military Police. The methodological design of this study is exploratory, as it provides greater familiarity with the subject matter. The results highlighted the importance of complying with SOPs to ensure safety, justice, and proper accountability in police operations, in accordance with human rights. It was also found that noncompliance with these procedures may lead to serious consequences, including exposure to life-threatening risks during police incidents, especially when using differentiated levels of force. It is concluded that the implementation of SOPs in the Military Police system emerges as a strategy to optimize actions and promote the military doctrine in accordance with the law. However, the absence of implementation and practical testing prevented a complete evaluation of the feasibility and effectiveness of the proposal in different scenarios and routine situations faced by police forces.